Coordination and Digitalization Gaps in Rural Agribusiness: Case Studies from Indonesia's MSME Sector - Mintje, Quirina Ariantji Patrisia; Zulkarnain, Ahnis; Marjan, Yakuttinah; AN, Charles (Indonesian Scientific Publication, 2025)
Micro, Small, and Medium Enterprises (MSMEs) form the backbone of Indonesia’s agricultural economy, yet they face persistent inefficiencies in supply chain management (SCM), particularly in rural and coastal areas. This study examines the coordination and digitalization challenges that hinder SCM performance among agricultural MSMEs, using three case studies: Sidrap rice distribution, Malk Chips (processed taro), and Bunga Seroja (seaweed production). The SCOR (Supply Chain Operations Reference) model is employed to assess performance across five key processes: Plan, Source, Make, Deliver, and Return. A qualitative, case study approach was used, relying on secondary data from journal articles, government reports, and institutional studies. Comparative analysis was conducted to evaluate digital readiness, stakeholder coordination, and SCM performance metrics across the cases. Findings show that while Malk Chips benefits from partial digital adoption and efficient logistics practices, Sidrap and Bunga Seroja continue to rely on traditional models with limited integration of digital tools. Common issues include fragmented coordination, poor infrastructure, low digital literacy, and inadequate stakeholder engagement. These factors contribute to suboptimal performance in the Deliver, Make, and Return segments of the SCOR model. The study concludes that successful SCM digitalization in agricultural MSMEs requires localized, context sensitive interventions. These include mobile based communication platforms, peer learning models, and tailored policy frameworks that integrate the lived realities of rural enterprises. Such strategies can foster efficiency, transparency, and competitiveness in Indonesia’s agribusiness supply chains.